English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x+5y=20

3x-7y=42

2007-03-22 17:47:33 · 11 answers · asked by delsydoodles 1 in Science & Mathematics Mathematics

11 answers

Thats just solving for y. Since slope-intercept form is y = mx + b.

x + 5y = 20
=> 5y = -x + 20
=> y = -x/5 + 4

3x - 7y = 42
=> 7y = 3x - 42
=> y = 3/7x - 6

2007-03-22 17:52:31 · answer #1 · answered by Kraca 3 · 1 0

Slope-intercept form: y=mx+b, where m is the slope and b is the y intercept

x+5y=20
x+5y-x=20-x
5y/5= -x/5+20/5
y= (-1/5)x+4
The slope= -1/5, the y-intercept= 4

3x-7y=42
3x-7y-3x= -3x+42
-7y/-7= -3x/-7 + 42/-7
y= (3/7)x - 6
The slope= 3/7, the y-intercept= -6

2007-03-22 18:12:33 · answer #2 · answered by ellen z 1 · 0 0

1) y = (20 - x)/5

y = -x/5 + 4

Slope: -1/5. Intercept: 4

2)

y = (3x - 42)/7
y = 3x/7 - 6

Slope: 3/7
Intercept: -6

2007-03-22 17:53:34 · answer #3 · answered by Rafael Mateo 4 · 0 0

x + 5y = 20
5y = 20 - x
y = 4 - x/5
y = -1/5 x + 4

3x - 7y = 42
-7y = 42 - 3x
y = 42/-7 - 3x/-7
y = -6 + 3/7 x
y = 3/7 x - 6

2007-03-22 17:57:57 · answer #4 · answered by rooster1981 4 · 0 0

Instead of telling you the answer, these people should be helping you learn what slope-intercept means.

Slope intercept equations have the form y=mx +b, where m is the slope of a line. The first thing you should do is get the y-variable on the opposite side of the equation from the x-variable.

ax+by = c turns into:
-ax+ax+by = c-ax
0+by = c-ax

Then you divide by the coefficient, in this case b.

by/b = (c-ax)/b
y = c/b-(a/b)x

2007-03-22 17:56:50 · answer #5 · answered by existenz48162 3 · 0 0

5y = 20 - x
y = (20 - x)/5
y = -(x/5) + 4

-7y = 42 - 3x
y = (42 - 3x)/-7
y = -6 + 3/7x
y = (3/7x) - 6

good ol' algebra lol

2007-03-22 17:55:18 · answer #6 · answered by Anonymous · 0 0

slope intercept forms are forms which have y on one side and the rest equation on the otherside.
So the first one will be:
y= -1/5 x + 4
second one:
y= 3/7x - 6

2007-03-22 17:52:39 · answer #7 · answered by Anonymous · 1 0

y = 4 - 1/5x

y = 3/7x - 6

2007-03-22 17:51:16 · answer #8 · answered by Jimmy Dean 4 · 0 0

y=(-x+20)/5
y=(3x-42)/7

2007-03-22 17:53:03 · answer #9 · answered by djin 2 · 0 0

y= -1/5x +4

y= 3/7x - 6

2007-03-22 17:51:12 · answer #10 · answered by jacobm_24 2 · 0 0

fedest.com, questions and answers